Β-Asarone Protects PC12 Cells Against Hypoxia-Induced Injury Via Negatively Regulating RPPH1/MiR-542-3p/DEDD2 Axis. (April 2022) - Yang, Fan; Duan, Hongyu; Ye, Nannan; Zeng, Yu; Yang, Pengxiang; Shao, Bo; Wang, Chunyu; Lin, Gaojun
Hypoxic injury to the brain is very intricate under the control of biochemical reactions induced by various factors and mechanisms. Long non-coding RNAs (lncRNAs) have already been revealed to affect pathological processes in the nervous system of different degrees. This research aimed to investigate the mechanisms implicated in hypoxic brain injury. β-Asarone mitigated the decrease of cell viability, superoxide dismutase activity, and mitochondrial membrane potential, as well as the increase of cell apoptosis, lactate dehydrogenase release, malondialdehyde content, and reactive oxidative species production by cobalt chloride. LncRNA ribonuclease P RNA component H1 (RPPH1) was discovered to be highly expressed in hypoxia-induced PC12 cells, and β-Asarone addition led to a decline in RPPH1 expression. RPPH1 overexpression reversed the effect of β-Asarone on hypoxia-induced injury in PC12 cells. Furthermore, we proved that RPPH1 could sponge miR-542-3p. Subsequently, death effector domain containing 2 (DEDD2) was proven as the downstream gene of RPPH1/miR-542-3p axis. Eventually, the whole regulation mechanism of RPPH1/miR-542-3p/DEDD2 axis was testified through rescue assays. The impacts of β-Asarone on hypoxia-induced PC12 cells could be countervailed by RPPH1 augment, which was also discovered to be neutralized in response to miR-542-3p overexpression or DEDD2 depletion. These findings offered a novel perspective for understanding neuroprotection.